PERAN AUDITOR INTERNAL SEBAGAI WATCHDOG, CONSULTANT, ATAU CATALYST? STUDI KASUS DI UNIVERSITAS SURABAYA - Erwin Christianto; Bonnie Soeherman (Perpustakaan Universitas Surabaya, 2018)
Now a day, the development of information technology has led to increased business competition. Internal auditors become strategic figures for an organization. There are three roles of internal auditors regarding the paradigm shift about role of internal auditors that is watchdogs, consultants, and catalysts. Therefore, the organizers' perceptions/views on internal auditors are considered very important as they may affect support for the scope of activities and impacts provided by the internal auditor on the organization. To find out the perceptions of the leadership of the University of Surabaya, the researchers conducted interviews and questionnaires to five resource persons consisting of rector, director of quality assurance and internal audit, dean of business and economics faculty, head of management department of business and economics faculty, and coordinator of quality guarantee of study program faculty of business and economics of the University of Surabaya. The researcher tries to examine the auditee's perception on the function and role of internal auditor and find the cause of the perception. The results of this thesis final project shows that the current internal auditor still acts as a watchdog, limited on identifying all accounts in the financial statements and checking the accounts thoroughly. On the other hand, the auditee has a perception and hopes that the internal auditor should act as a catalyst who conducts internal audit with empathy, cares the auditee’s feeling and becomes a facilitator for better auditee development.